(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
This interview, taken in New York City on August 2012, is based on Richard Schechner’s experience at the department of Performance Studies, New York University. He talks about the changes occurred since the time he contributed to create the department in the early 80s. This conversation also gives a brief overview of Schechner’s focus on the concept of performance, and on the relationship between theory and practice in “his” Performance Studies.